Determination Of The Difference Handrub Boiled Betel Leaf (Piper Betle) Compared Alcohol On The Percentage Of Reducing The Number Of Microorganism Colony - pramesti, kadesha (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2025)
tel leaf (Piper Betle Linn) is one of the natural ingredients that can be used as a substitute for alcohol in hand sanitizers. This study aims to analyze the differences in handrubs from boiled betel leaves (Piper betle) compared to 70% alcohol on the percentage of reduction in the number of microorganism colonies. The type of research conducted was experimental research with a Pre Post Test Group Design research design. Sampling was carried out by Concutive Sampling from Students of the Faculty of Medicine, Sultan Agung Islamic University, Semarang through the glove juice method with a total of 20 samples per group. Data on the percentage of reduction in the number of microorganism colonies between the handrub group boiled betel leaves (Piper betle) compared to 70% alcohol were analyzed using Mann Whitney. The results of the study found that 70% alcohol handrub was better than handrub boiled betel leaves (Piper betle Linn) with a difference in handrub boiled betel leaves of 39.46% and handrub 70% alcohol of 59.18%. So it is concluded that there is a significant difference between handrub boiled betel leaves (Piper betle) compared to 70% alcohol.